Phosphorus speciation under long-term crop rotation management in a tropical soil - Rigon, João Paulo Gonsiorkiewicz; Crusciol, Carlos Alexandre Costa [UNESP]; Calonego, Juliano Carlos [UNESP]; Gatiboni, Luciano Colpo; Pavinato, Paulo Sérgio; Colzato, Marina; Capuani, Silvia [UNESP]; Rosolem, Ciro Antonio [UNESP] (Wiley, 2024)
Crop rotation and soil management practices after native tropical forest conversion may impact the dynamics of inorganic and organic phosphorus (Pi and Po) species in the soil. By combining the state-of-the-art spectroscopic methods P K-edge X-ray absorption near edge structure (XANES), 31P liquid nuclear magnetic resonance (31P-NMR) and chemical P fractionation, this study provides important insights on soil P speciation after conversion of native forest to cropland under distinct managements. A field trial was conducted in a weathered tropical soil to assess Pi and Po changes after conversion of native forest to cropland. The crop rotations were managed under no-tillage (NT) or minimum tillage (MT) since 2003, and repeated annually until 2015, cropped in the fall–winter and spring seasons, followed by soybean in the summer. Soil XANES analysis in the end revealed that P was predominantly associated with ferrihydrite and hematite, suggesting that P speciation was more strongly influenced by the presence of iron(oxyhydr)oxide than by crop rotations and/or soil management. The conversion of native forest to cropland promoted the mineralization of Po species, leading to re-adsorption in non-labile forms and consequently worsening the P cycling in the system. To increase the labile P pools and supply crop P demand, inputs of inorganic fertilizers were required owing to the strong soil P sorption. Our results show that even conservation practices such as MT or NT and complex crop rotations are not sufficient to inhibit the impact of cropland conversion on soil P forms.
Keywords: forest conversion; no-tillage; soil management; sustainable P management